Biomechanical factors associated with running economy and performance of elite Kenyan distance runners: A systematic review - Tawa, N.; Louw, Q. (Journal of Bodywork and Movement Therapies, 2018)
Running economy (RE) is a determinant of performance in endurance sports and is a complex multi-factorial measure which reflects the combined functioning of bio-mechanical, neuro-muscular, metabolic and cardio-respiratory factors some of which are hereditary or adapt to coaching.